Film as a radical pedagogic tool - O'Neill, Deirdre (Routledge studies in education, neoliberalism, and Marxism, 2018)
Radical pedagogy, prison and film -- Working class subjectivity and representation -- Broadening the referential framework: prison as an event -- Hegemony and the culture of the working class -- Radical cinematic practices -- The foodbank film -- -- Conclusion.